To solve the equation and find the correct expression for \( y \), let's start with the first equation you've provided:
Step 1: Rearranging the equation
The equation is: \[ 16 = -5x - 9y \]
To isolate \( y \), we can rearrange it. First, let's move both terms involving \( x \) and \( y \) to one side:
\[ -9y = 16 + 5x \]
Now, divide everything by \(-9\) to solve for \( y \):
\[ y = -\frac{16 + 5x}{9} \]
Now, we can break that down:
\[ y = -\frac{5x}{9} - \frac{16}{9} \]
Step 2: Finding a different form
Next, we can rewrite that in a form close to what you mentioned:
Rewrite it as:
\[ y = -\frac{5}{9}x - \frac{16}{9} \]
To get a common factor that matches your expression \( y = \frac{5}{4}x - \frac{16}{6} \):
We need to multiply through by \(-\frac{4}{5}\):
\[ y = \frac{5}{4}x - \frac{16}{6} \]
Step 3: Plugging in \( x = -2 \)
Now, plug the value \( x = -2 \) into the new equation:
\[ y = \frac{5}{4}(-2) - \frac{16}{6} \]
Calculating this gives:
\[ y = -\frac{10}{4} - \frac{16}{6} \] \[ y = -\frac{5}{2} - \frac{8}{3} \]
Now, let's find a common denominator to combine these fractions. The least common multiple of \( 2 \) and \( 3 \) is \( 6 \):
Convert \( -\frac{5}{2} \) to sixths:
\[ -\frac{5}{2} = -\frac{15}{6} \]
Now add:
\[ y = -\frac{15}{6} - \frac{8}{3} = -\frac{15}{6} - \frac{16}{6} = -\frac{31}{6} \]
This does not give you what you've specified. There may be a misunderstanding in the terms of the problem.
If you are looking for the final value where \( y = -\frac{2}{3} \), that means you have a different expression or particular context. Purely based on the set up and steps, the derived equation does not lead to that specific output.
Make sure to clarify if you are looking for a different form or based on a different initial equation! If you can offer more context, I can assist you further.